Unsteady aerodynamic response of the rotor blades of an axial flow compressor operating under conditions of circumferential inlet distortions and rotating stall - Ozcanli, S. C. (Cranfield University, 1983)
The aim of this work is to study the unsteady response of rotor blades of a lightly loaded single stage axial flow compressor experiencing inlet flow distortions in forms of circumferential pressure distortions and rotating stall . Recent developments in pressure transducer and microprocessor technology have enabled the research scientist to study the aerodynamic behaviour of rotor blades . Two rotor blades of the axial flow compressor have been instrumented with sixteen miniature pressure transducers , eight of which are on the pressure surface of one of the blades , while the remaining eight are on the suction surface of the other blade . An on-line microprocessor based data acquisition system has been developed to record simultaneously , measurements from each blade . Four different circumferential wire mesh screens of different extents and densities were employed at a distance of one chord length upstream from the blade leading edge to generate circumferential square wave pressure distortions . Also the compressor was run under conditions in the rotating stall regime . Flow parameters ahead of the rotor have been measured by using high response 3-hole cylindrical probes and a conventional 3-hole wedge probe . The values of the dynamic normal force coefficient were derived from instantaneous wall static pressure measurements on the two blade surfaces . The results obtained from the experiments were compared with the theoretical predictions.